A method for improving the low-temperature catalytic activity of a manganese-based catalyst

CN122999175APending Publication Date: 2026-10-30ZHEJIANG BINGCHONG ENVIRONMENT PROTECTION TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610915558.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-24
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]有鉴于现有技术的上述缺陷,本发明所要解决的技术问题是:在室温甚至高湿条件下,现有锰基催化剂对臭氧的活化效率低、对含氯等典型室内VOCs的深度矿化能力不足,且在臭氧和水汽共存环境中易发生表面氯物种积累和活性位钝化,导致低温催化活性差、CO2选择性低及臭氧滑脱严重,难以兼顾高效净化与臭氧安全利用,因此亟需提供一种通过界面精细构筑显著提升锰基催化剂低温活性、矿化能力和长期稳定性的制备方法

Benefits of technology

[0019]在室温及高湿条件下,对甲醛、甲苯和含氯芳香族VOCs均表现出显著高于现有锰基/钛基催化剂的去除率和CO2选择性,适用于典型室内空气净化工况。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999175A_ABST
    Figure CN122999175A_ABST
Patent Text Reader

Abstract

The present application relates to a manganese-based catalyst preparation method for indoor air purification. The alpha-MnO2 carrier containing tunnel cation vacancies is prepared by a hydrothermal method, and after being activated by alkali treatment, the metal titanium alkoxide-organic complexing agent system is used for limited hydrolysis in the aqueous organic solvent, so that the Ti species is grafted to build the Mn-O-Ti interface, and further, the rhenate, nickel salt or tungstate is fixed in the vicinity of the interface with high dispersion to form the Mn-O-Ti-M composite interface catalyst. The catalyst has high removal rate and high CO2 selectivity for formaldehyde, toluene and chlorine-containing aromatic VOCs under room temperature and high humidity conditions, can efficiently utilize and consume ozone, inhibit surface chlorine poisoning, and exhibits excellent water resistance and long-time stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of metal oxide catalyst technology, and in particular to a method for improving the low-temperature catalytic activity of manganese-based catalysts. Background Technology

[0002] Volatile organic compounds (VOCs) in indoor air, such as formaldehyde, aromatic hydrocarbons, and some chlorinated organic compounds, are among the most significant pollutants affecting the health of residential and office environments. Compared to industrial waste gas, indoor VOCs are characterized by lower concentrations, more complex compositions, temperatures close to room temperature, and higher relative humidity. This places higher demands on the activity, stability, and safety (such as ozone residue) of catalytic materials under low-temperature and high-humidity conditions. Traditional adsorption materials suffer from limited capacity and difficulty in regeneration; while high-temperature catalytic combustion exhibits good activity, it is unsuitable for low-temperature indoor conditions. Therefore, developing a manganese-based catalytic system suitable for indoor air purification, capable of efficiently removing VOCs and safely utilizing ozone under both room temperature and high humidity conditions, is of great significance.

[0003] CN120693209A discloses a manganese-containing titanium oxide composite catalyst and a method for removing odors. This technology introduces manganese into TiO2 to regulate its UV-Vis absorption characteristics and the proportion of surface-active oxygen species, obtaining a composite catalyst for removing odors (including some VOCs) in humid environments. This catalyst shows some removal efficiency for formaldehyde and methanethiol under low-temperature and humid conditions, and exhibits improved moisture resistance. However, this technology is not specifically optimized for ozone-assisted oxidation in indoor air purification scenarios, and it does not adequately address ozone utilization efficiency, ozone slippage, deep mineralization of chlorine-containing VOCs, and resistance to chlorine poisoning.

[0004] CN115382535A discloses a method for preparing a manganese-based cerium-zirconium solid solution that can replace noble metals in VOC catalysts. This technique involves preparing a Ce-Zr-La-Y solid solution and then highly dispersing a perovskite structure (La) on its surface. X Y 1-X MnO3 is used to form a Mn-Ce-Zr multi-component composite oxide for the catalytic combustion of VOCs such as toluene under medium-to-high temperature conditions (300-500℃), thereby reducing the amount and cost of precious metals used in industrial exhaust gas treatment. This system exhibits good ignition and complete conversion temperatures under high-temperature conditions, but its operating temperature range is significantly high, primarily targeting the catalytic combustion of industrial waste gases. Its design relies on Ce-Zr oxygen storage and release behavior and high-temperature red oxygen circulation, making it unsuitable for indoor air purification conditions close to room temperature and high humidity. Furthermore, this technology does not involve room-temperature catalytic oxidation systems involving ozone, nor does it consider the accumulation of intermediates and surface poisoning control of chlorine-containing VOCs in low-temperature, high-humidity, and ozone-coexisting environments. Summary of the Invention

[0005] In view of the above-mentioned deficiencies of the prior art, the technical problem to be solved by the present invention is that: under room temperature or even high humidity conditions, existing manganese-based catalysts have low activation efficiency for ozone and insufficient deep mineralization ability for typical indoor VOCs such as chlorine-containing catalysts. Moreover, in the coexistence of ozone and water vapor, surface chlorine species are prone to accumulation and passivation of active sites, resulting in poor low-temperature catalytic activity, low CO2 selectivity and serious ozone slippage, making it difficult to achieve both high-efficiency purification and safe utilization of ozone. Therefore, there is an urgent need to provide a preparation method that can significantly improve the low-temperature activity, mineralization ability and long-term stability of manganese-based catalysts through fine interfacial construction.

[0006] To achieve the above objectives, this invention provides a method for enhancing the low-temperature catalytic activity of manganese-based catalysts: First, an α-MnO2 support is prepared by hydrothermal synthesis and calcination, and then surface-activated by an alkaline aqueous solution; subsequently, a titanium alkoxide-organic complexing agent system is used to achieve restricted hydrolysis and in-situ nucleation in an aqueous organic solvent, grafting Ti species onto the activated α-MnO2 surface to construct a strong Mn-O-Ti coupling interface; based on this, rhenium salts, nickel salts, or tungstates are used to adsorb, undergo restricted hydrolysis, and calcination to highly disperse and anchor Re, Ni, or W near the Ti-MnO2 interface, forming a Mn-O-Ti-M (M is Re, Ni, or W) composite interface, thereby significantly enhancing ozone activation capacity and low-temperature VOCs mineralization performance under room temperature and high humidity conditions.

[0007] The specific technical solution is as follows:

[0008] A method for improving the low-temperature catalytic activity of manganese-based catalysts includes the following steps:

[0009] S1: Dissolve 3.0-4.0 g manganese sulfate monohydrate, 4.0-5.0 g ammonium persulfate, and 10.0-18.0 g ammonium sulfate in 80-140 mL of water. Stir vigorously at room temperature for 0.1-1.0 h, then transfer to a hydrothermal reactor and react hydrothermally at 100-140 °C for 8-24 h. After cooling to room temperature, filter, wash, and dry, then heat to 350-450 °C in air at 2-10 °C / min and hold for 2-6 h to obtain α-MnO2 support containing tunnel cation vacancies.

[0010] S2: Disperse 1.5-3.0 g of the α-MnO2 support containing tunneled cation vacancies obtained in step S1 in 100-500 mL of water, add 20-100 mL of 0.5-2.0 wt% NaOH aqueous solution, and stir at room temperature for 0.5-2.0 h; filter and wash to obtain a moistened activated support; during the hydrothermal reaction, an α-MnO2 crystal framework with a 2×2 tunnel structure is formed, and the NH4+ in the reaction system... 4+Cations can temporarily enter the tunnel structure to stabilize crystal formation. During subsequent calcination, some tunnel cations decompose or are removed, creating unoccupied sites in the α-MnO2 tunnels, thus obtaining an α-MnO2 support containing tunnel cation vacancies. These tunnel cation vacancies can provide more defect sites and adsorption sites, which is beneficial for the subsequent dispersion and loading of active components and enhances the material's ability to capture alkali metal ions.

[0011] S3. Add 0.2-0.8 g of tetraisopropyl titanate to 50-150 mL of anhydrous ethanol, add 0.05-0.30 g of acetylacetone, and stir at room temperature for 10-30 min to obtain a titanium precursor complex solution; add the wetted activated carrier obtained in step S2 to the titanium precursor complex solution, sonicate for 5-30 min, and stir at room temperature for 20-60 min; then add 30-80 g of 80-95 wt% ethanol aqueous solution dropwise at a rate of 0.5-2.0 mL / min, and continue stirring at room temperature for 1-5 h after the addition is complete; filter, wash, and dry.

[0012] Alternatively, add 0.2-0.8 g of tetraisopropyl titanate to 50-150 mL of anhydrous ethanol, add 0.05-0.30 g of acetylacetone, and stir at room temperature for 10-30 min to obtain a titanium precursor complex solution; add the moistened activated carrier obtained in step S2 to the titanium precursor complex solution, sonicate for 5-30 min, and stir at room temperature for 20-60 min; then add 30-80 g of 80- Add a 95wt% aqueous ethanol solution dropwise, and continue stirring at room temperature for 1-5 hours after the addition is complete. Filter, wash, and dry the solution, then add it to an ethanol solution containing ammonium perrhenate, nickel nitrate, or ammonium metatungstate. Sonicate the solution at room temperature for 5-30 minutes and stir for 20-60 minutes. Then add 30-80g of an 80-95wt% aqueous ethanol solution dropwise at a rate of 0.5-2.0mL / min. After the addition is complete, continue stirring at room temperature for 1-5 hours. Filter, wash, and dry the solution.

[0013] S4 The solid dried in step S3 is heated to 350-450℃ in air at a rate of 2-10℃ / min and held for 2-6 hours to obtain a manganese-based composite catalyst.

[0014] Preferably, in step S1, the hydrothermal reaction temperature is 110-130℃ and the hydrothermal time is 10-16h; the drying temperature is 90-110℃ and the drying time is 10-16h; the calcination heating rate is 3-7℃ / min, the calcination temperature is 380-420℃, and the calcination time is 3-5h.

[0015] Preferably, the solution containing ammonium perrhenate, nickel nitrate or ammonium metatungstate in step S3 is an ethanol solution with a mass fraction of 0.005-0.5 wt%.

[0016] Preferably, the mass fraction of the ammonium perrhenate solution is 0.01-0.05 wt%, most preferably 0.02 wt%; the mass fraction of the nickel nitrate solution is 0.05-0.2 wt%, most preferably 0.1 wt%; and the mass fraction of the ammonium metatungstate solution is 0.05-0.2 wt%, most preferably 0.1 wt%.

[0017] Preferably, the calcination temperature in step S4 is 380-420℃, most preferably 400℃, and the calcination time is 3-5h, most preferably 4h.

[0018] The beneficial effects of this invention are:

[0019] Under room temperature and high humidity conditions, it exhibits significantly higher removal rates and CO2 selectivity for formaldehyde, toluene, and chlorinated aromatic VOCs than existing manganese / titanium-based catalysts, making it suitable for typical indoor air purification conditions.

[0020] By constructing a strong Mn-O-Ti coupling interface through complexation and restricted hydrolysis, and introducing additives such as Re, Ni, or W on it with high dispersion, the ozone activation efficiency and VOCs deep mineralization capacity are effectively improved, the outlet ozone concentration is significantly reduced, and the efficient and safe utilization of ozone is achieved.

[0021] By utilizing the α-MnO2 support in conjunction with the Mn-O-Ti-M composite interface, the accumulation of chlorine-containing intermediate species on the surface can be inhibited, maintaining a high proportion of active Mn. 3+ It exhibits excellent water resistance, chlorine poisoning resistance, and long-term operational stability due to its presence of defective oxygen sites.

[0022] The preparation method has clear steps and mild conditions. It uses conventional inorganic salts and metal alkoxide precursors, and the process has good scalability, making it suitable for the preparation of small-scale and large-scale catalysts for indoor air purification filter elements. Attached Figure Description

[0023] Figure 1 The XPS full spectrum analysis of the manganese-based composite catalyst obtained by the method of improving the low-temperature catalytic activity of manganese-based catalyst in Example 1 shows the elemental signals of Mn, O and Ti. The appearance of the Ti 2p peak proves that the Ti species was successfully grafted onto the surface of the α-MnO2 support.

[0024] Figure 2 This is the XPS full spectrum analysis of the manganese-based composite catalyst obtained by the method for improving the low-temperature catalytic activity of manganese-based catalysts in Example 2, compared with... Figure 1In addition to the Mn, O, and Ti signals, a Re 4f characteristic peak was also observed, indicating that the Re species had been successfully introduced and dispersed near the Ti-MnO2 interface. Detailed Implementation

[0025] Example 1

[0026] A method for improving the low-temperature catalytic activity of manganese-based catalysts includes the following steps:

[0027] S1 3.380 g manganese sulfate monohydrate, 4.564 g ammonium persulfate and 13.214 g ammonium sulfate were dissolved in 100 mL of deionized water and stirred vigorously at room temperature for 0.5 h; transferred to a 200 mL hydrothermal reactor and hydrothermally reacted at 120 °C for 12 h; cooled to room temperature and filtered, washed 5 times with deionized water, dried at 100 °C for 12 h, then heated to 400 °C in air at 5 °C / min and calcined at 400 °C for 4 h to obtain α-MnO2 support containing tunnel cation vacancies;

[0028] S2 Take 1.900g of the α-MnO2 support containing tunneled cation vacancies obtained in step S1 and disperse it in 200mL of deionized water. Add 50mL of 1.0wt% NaOH aqueous solution and stir at room temperature for 1h. After filtration, wash with deionized water 3 times to obtain a moistened activated support.

[0029] S3. Add 0.356 g of tetraisopropyl titanate to 80 mL of anhydrous ethanol, then add 0.120 g of acetylacetone, and stir at room temperature for 15 min to obtain a titanium precursor complex solution. Add the wetted activated carrier obtained in step S2 to the titanium precursor complex solution, sonicate for 10 min, and stir at room temperature for 30 min. Continue to add 50 g of 90 wt% ethanol aqueous solution at a rate of 1.0 mL / min, and continue stirring at room temperature for 3 h after the addition is complete. After filtration, wash with anhydrous ethanol and deionized water once each, and dry at 60 °C for 12 h.

[0030] S4 The solid dried in step S3 is placed in an air atmosphere and heated to 400℃ at a rate of 2℃ / min, and kept at that temperature for 4h to obtain a manganese-based composite catalyst.

[0031] Comparative Example 1

[0032] A method for improving the low-temperature catalytic activity of manganese-based catalysts includes the following steps:

[0033] S1 3.380 g manganese sulfate monohydrate, 4.564 g ammonium persulfate and 13.214 g ammonium sulfate were dissolved in 100 mL of deionized water and stirred vigorously at room temperature for 0.5 h; transferred to a 200 mL hydrothermal reactor and hydrothermally reacted at 120 °C for 12 h; cooled to room temperature and filtered, washed 5 times with deionized water, dried at 100 °C for 12 h, then heated to 400 °C in air at 5 °C / min and calcined at 400 °C for 4 h to obtain α-MnO2 support containing tunnel cation vacancies;

[0034] S2 Take 1.900g of the α-MnO2 support containing tunneled cation vacancies obtained in step S1 and disperse it in 200mL of deionized water. Add 50mL of 1.0wt% NaOH aqueous solution and stir at room temperature for 1h. After filtration, wash with deionized water 3 times to obtain a moistened activated support.

[0035] S3. Add 0.356 g of tetraisopropyl titanate to 80 mL of anhydrous ethanol and stir at room temperature for 15 min to obtain a titanium precursor solution. Add 5.0 mL of deionized water dropwise at a rate of 1.0 mL / min and stir at room temperature for 30 min to rapidly hydrolyze the titanium precursor to form TiO2 sol. Add the moistened activation support obtained in step S2 and stir at room temperature for 3 h. After filtration, wash with anhydrous ethanol and deionized water once each, and dry at 60 °C for 12 h.

[0036] S4 The solid dried in step S3 is placed in an air atmosphere and heated to 400℃ at a rate of 2℃ / min, and kept at that temperature for 4h to obtain a manganese-based composite catalyst.

[0037] The raw material amounts, Ti loading, and calcination conditions were the same for Example 1 and Comparative Example 1, with the only difference being the loading method: Example 1 used acetylacetone complexation, ethanol dilution, and dropwise restricted hydrolysis, which made Ti species tend to nucleate / graft in situ on the MnO2 surface, making it easier to form a characterizable Mn-O-Ti strongly coupled interface / heterojunction; Comparative Example 1 used no complexation and rapid hydrolysis to nucleate first, which was more inclined to form TiO2 particles and then make physical contact with MnO2.

[0038] Example 2

[0039] A method for improving the low-temperature catalytic activity of manganese-based catalysts includes the following steps:

[0040] S1 3.380 g manganese sulfate monohydrate, 4.564 g ammonium persulfate and 13.214 g ammonium sulfate were dissolved in 100 mL of deionized water and stirred vigorously at room temperature for 0.5 h; transferred to a 200 mL hydrothermal reactor and hydrothermally reacted at 120 °C for 12 h; cooled to room temperature and filtered, washed 5 times with deionized water, dried at 100 °C for 12 h, then heated to 400 °C in air at 5 °C / min and calcined at 400 °C for 4 h to obtain α-MnO2 support containing tunnel cation vacancies;

[0041] S2 Take 1.900g of the α-MnO2 support containing tunneled cation vacancies obtained in step S1 and disperse it in 200mL of deionized water. Add 50mL of 1.0wt% NaOH aqueous solution and stir at room temperature for 1h. After filtration, wash with deionized water 3 times to obtain a moistened activated support.

[0042] S3. Add 0.356 g of tetraisopropyl titanate to 80 mL of anhydrous ethanol, then add 0.120 g of acetylacetone, and stir at room temperature for 15 min to obtain a titanium precursor complex solution. Add the wetted activated carrier obtained in step S2 to the titanium precursor complex solution, sonicate for 10 min, and stir at room temperature for 30 min. Continue to add 50 g of 90 wt% ethanol aqueous solution at a rate of 1.0 mL / min, and continue stirring at room temperature for 3 h after the addition is complete. After filtration, wash with anhydrous ethanol and deionized water once each, dry at 60 °C for 12 h, and then add to 50 g of... In a 0.02 wt% ammonium perrhenate ethanol solution, the mixture was ultrasonically dispersed for 10 min, then stirred at room temperature for 30 min to ensure that the Re precursor was fully contacted and adsorbed onto the Ti-MnO2 surface. 50 g of 90 wt% ethanol aqueous solution was added dropwise at a rate of 1.0 mL / min, and stirring was continued at room temperature for 3 h after the addition was complete. After filtration, the mixture was washed once with anhydrous ethanol and once with deionized water, and then dried at 60 °C for 12 h.

[0043] S4 The solid dried in step S3 is placed in an air atmosphere and heated to 400℃ at a rate of 2℃ / min, and kept at that temperature for 4h to obtain a manganese-based composite catalyst.

[0044] Example 3

[0045] A method for improving the low-temperature catalytic activity of manganese-based catalysts includes the following steps:

[0046] S1. Dissolve 3.380 g manganese sulfate monohydrate, 4.564 g ammonium persulfate and 13.214 g ammonium sulfate in 100 mL of deionized water and stir vigorously at room temperature for 0.5 h. Transfer to a 200 mL hydrothermal reactor and hydrothermally react at 120 °C for 12 h. After cooling to room temperature, filter, wash 5 times with deionized water, dry at 100 °C for 12 h, and then heat to 400 °C in air at 5 °C / min and calcine at 400 °C for 4 h to obtain α-MnO2 support containing tunnel cation vacancies.

[0047] S2 Take 1.900g of the α-MnO2 support containing tunneled cation vacancies obtained in step S1 and disperse it in 200mL of deionized water. Add 50mL of 1.0wt% NaOH aqueous solution and stir at room temperature for 1h. After filtration, wash with deionized water 3 times to obtain a moistened activated support.

[0048] S3. Add 0.356 g of tetraisopropyl titanate to 80 mL of anhydrous ethanol, then add 0.120 g of acetylacetone, and stir at room temperature for 15 min to obtain a titanium precursor complex solution. Add the wetted activated carrier obtained in step S2 to the titanium precursor complex solution, sonicate for 10 min, and stir at room temperature for 30 min. Continue to add 50 g of 90 wt% ethanol aqueous solution at a rate of 1.0 mL / min, and continue stirring at room temperature for 3 h after the addition is complete. After filtration, wash with anhydrous ethanol and deionized water once each, dry at 60 °C for 12 h, and then add to 50 g of... In a 0.1 wt% nickel nitrate ethanol solution, the mixture was ultrasonically dispersed for 10 min, then stirred at room temperature for 30 min to ensure that the Ni precursor was fully contacted and adsorbed onto the Ti-MnO2 surface. 50 g of 90 wt% ethanol aqueous solution was added dropwise at a rate of 1.0 mL / min. After the addition was complete, the mixture was stirred at room temperature for 3 h. After filtration, the mixture was washed once with anhydrous ethanol and once with deionized water, and then dried at 60 °C for 12 h.

[0049] S4 The solid dried in step S3 is placed in an air atmosphere and heated to 400℃ at a rate of 2℃ / min, and kept at that temperature for 4h to obtain a manganese-based composite catalyst.

[0050] Example 4

[0051] A method for improving the low-temperature catalytic activity of manganese-based catalysts includes the following steps:

[0052] S1 3.380 g manganese sulfate monohydrate, 4.564 g ammonium persulfate and 13.214 g ammonium sulfate were dissolved in 100 mL of deionized water and stirred vigorously at room temperature for 0.5 h; transferred to a 200 mL hydrothermal reactor and hydrothermally reacted at 120 °C for 12 h; cooled to room temperature and filtered, washed 5 times with deionized water, dried at 100 °C for 12 h, then heated to 400 °C in air at 5 °C / min and calcined at 400 °C for 4 h to obtain α-MnO2 support containing tunnel cation vacancies;

[0053] S2 Take 1.900g of the α-MnO2 support containing tunneled cation vacancies obtained in step S1 and disperse it in 200mL of deionized water. Add 50mL of 1.0wt% NaOH aqueous solution and stir at room temperature for 1h. After filtration, wash with deionized water 3 times to obtain a moistened activated support.

[0054] S3. Add 0.356 g of tetraisopropyl titanate to 80 mL of anhydrous ethanol, then add 0.120 g of acetylacetone, and stir at room temperature for 15 min to obtain a titanium precursor complex solution. Add the wetted activated support obtained in step S2 to the titanium precursor complex solution, sonicate for 10 min, and stir at room temperature for 30 min. Continue to add 50 g of 90 wt% ethanol aqueous solution at a rate of 1.0 mL / min, and continue stirring at room temperature for 3 h after the addition is complete. After filtration, wash once with anhydrous ethanol and once with deionized water, dry at 60 °C for 12 h, and then add to 50 g of 0.1 wt% ammonium metatungstate ethanol solution. Sonicate for 10 min, and stir at room temperature for 30 min to ensure that the W precursor fully contacts and adsorbs onto the Ti-MnO2 surface. Continue to add 50 g of ethanol aqueous solution at a rate of 1.0 mL / min. After adding 90 wt% ethanol aqueous solution, continue stirring at room temperature for 3 h; after filtration, wash with anhydrous ethanol and deionized water once each, and dry at 60 °C for 12 h.

[0055] S4 The solid dried in step S3 is placed in an air atmosphere and heated to 400℃ at a rate of 2℃ / min, and kept at that temperature for 4h to obtain a manganese-based composite catalyst.

[0056] Test Example 1

[0057] Low-temperature catalytic activity testing of catalysts for typical indoor VOCs

[0058] The manganese-based composite catalysts prepared in the examples and comparative examples were tested for low-temperature catalytic performance in a fixed-bed microreactor under the following specific conditions:

[0059] 1) Loading and Conditions

[0060] Catalyst loading: 50mg (50 mesh), mixed with quartz sand at a mass ratio of 1:4 and loaded into a quartz tube with an inner diameter of 6mm to form a 30mm catalyst bed.

[0061] Reaction temperature: 25℃; relative humidity: 60%RH; total inlet flow rate: 300mL / min, corresponding to a space velocity of 360,000mL / (g·h). Atmosphere composition: mainly air, containing target VOCs and a small amount of ozone.

[0062] 2) Target VOCs and their concentrations

[0063] Formaldehyde: 0.5 ppm; Toluene: 0.5 ppm; Chlorobenzene: 0.5 ppm; the remainder is air and water vapor, with an oxygen volume fraction of 20 vol.%.

[0064] 3) Oxidizing agent conditions

[0065] Inlet ozone concentration: 0.5 ppm (generated by an external ozone generator, mixed into the intake air, and all passes through the catalytic bed).

[0066] 4) Analytical methods

[0067] VOCs and intermediates: Gas chromatography (GC-FID / GC-MS).

[0068] CO2, CO: Non-dispersive infrared absorption method (NDIR);

[0069] Ozone: Ultraviolet absorption ozone analyzer.

[0070] 5) Characteristic Indicators

[0071] VOC removal rate R (VOC, %):

[0072] R(VOC) = (C in -C out ) / C in ×100%

[0073] C in Inlet VOC concentration; C out Export VOC concentration.

[0074] CO2 selectivity S (CO2, %):

[0075]

[0076] △C CO2 =C CO2,out -C CO2,in CO2 concentration at the catalyst bed outlet minus the CO2 concentration at the inlet (background CO2)

[0077] nc: The number of carbon atoms in each VOC molecule (e.g., toluene has 7, and chlorobenzene has 6).

[0078] C in -C out The concentration of VOCs that were "removed" (same as the molecular part of R(VOC)).

[0079] Catalytic bed outlet ozone concentration C (O3,out) (ppm).

[0080] Under the above conditions, the concentrations of VOCs, CO2, and ozone at the inlet and outlet of the catalyst bed were recorded, and the average value of three consecutive collections after 2 hours of stable operation was compared.

[0081] Table 1 Comparison of catalytic performance under the conditions of 25℃, 60%RH, and O3=0.5ppm

[0082] Example 1 92.3 88.7 81.5 86.4 0.04 Comparative Example 1 54.8 47.2 32.9 51.6 0.27 Example 2 94.5 90.8 86.2 91.5 0.03 Example 3 93.0 89.1 83.7 87.5 0.04 Example 4 92.7 88.5 83.1 88.6 0.04

[0083] Under the same inlet VOC and ozone concentration conditions, Comparative Example 1 used a conventional fast hydrolysis supported TiO2 catalyst, which achieved removal rates of 54.8%, 47.2%, and 32.9% for formaldehyde, toluene, and chlorobenzene, respectively, with a CO2 selectivity of only 51.6% and an outlet ozone concentration of 0.27 ppm. This indicates that its low-temperature activity and mineralization capacity are poor, and its ozone utilization efficiency is low, with a large amount of ozone slipping off.

[0084] In contrast, Example 1 employed a Ti-supported method involving acetylacetone complexation, ethanol dilution, and restricted hydrolysis to construct a strongly coupled Mn-O-Ti interface. This resulted in improved removal rates of formaldehyde, toluene, and chlorobenzene to 92.3%, 88.7%, and 81.5%, respectively, with CO2 selectivity increasing to 86.4% and the outlet ozone concentration decreasing to 0.04 ppm. This demonstrates that the strongly coupled Mn-O-Ti interface significantly promotes the activation and conversion of ozone on the catalyst surface, enabling more ozone to participate in the deep oxidation of VOCs. This achieves higher removal and mineralization rates at room temperature and effectively inhibits ozone slippage.

[0085] Based on Example 1, the introduction of different additives, specifically Re in Example 2, Ni in Example 3, and W in Example 4, further improved the low-temperature catalytic activity of VOCs. In Example 3, Ni and W achieved removal rates of 93.0% / 92.7%, 89.1% / 88.5%, and 83.7% / 83.1% for formaldehyde, toluene, and chlorobenzene, respectively, with CO2 selectivity increasing to 87.5% and 88.6%, respectively. This indicates that conventional Ni and W additives have a certain promoting effect on ozone activation and intermediate product oxidation.

[0086] More notably, the catalyst introduced in Example 2 further improved the removal rates of formaldehyde, toluene, and chlorobenzene to 94.5%, 90.8%, and 86.2%, respectively, with a CO2 selectivity of 91.5%. This is not only significantly better than Example 1 without additives, but also better than the Ni and W system (Examples 3 and 4). At the same time, the outlet ozone concentration of Example 2 was 0.03 ppm, the lowest among the four examples, indicating that the Mn-O-Ti-Re composite interface has higher ozone utilization efficiency and stronger deep mineralization ability at room temperature.

[0087] It should be noted that the amount of rhenium additive added in Example 2 of this invention is controlled at an extremely low level, corresponding to a Re content in the catalyst that is much lower than the conventional precious metal loading. At such a low dosage, highly dispersed Re can be formed on the Mn-O-Ti interface, significantly improving ozone activation efficiency and VOCs deep mineralization capacity, exhibiting both high activity and high CO2 selectivity. The performance advantage of Example 2 mainly stems from the synergistic effect of the Mn-O-Ti-Re composite interface, rather than the accumulation of a large amount of precious elements.

[0088] Test Example 2

[0089] Stability and deactivation tolerance of catalysts under high humidity and room temperature conditions

[0090] Based on Test Example 1, the stability and deactivation tolerance of the manganese-based composite catalysts of Examples and Comparative Example 1 were further investigated under long-term operation and high humidity fluctuation conditions, with the following conditions set:

[0091] 1) Filling and environmental conditions

[0092] The catalyst loading method and loading amount are the same as in Test Example 1;

[0093] Reaction temperature: 25℃. Relative humidity: periodically varied between 40-80%RH, with each humidity plateau maintained for 4 hours, repeated cyclically. Total test duration: 100 hours.

[0094] 2) Intake composition and airspeed

[0095] Formaldehyde: 0.5 ppm; Toluene: 0.5 ppm; Chlorobenzene: 0.5 ppm; Inlet ozone concentration: 0.5 ppm; Space velocity: 36000 mL / (g·h), consistent with test example 1.

[0096] 3) In the test procedure, a mixed gas is introduced, and the catalyst is pre-run for 2 hours to reach stability;

[0097] The process is repeated in the following order: RH = 40% → 60% → 80% → 60% → 40% until a total of 100 hours of operation is completed. The removal rate of each VOC, the selectivity of CO2, and the ozone concentration at the outlet are recorded every 10 hours.

[0098] 4) Characteristic Indicators

[0099] After long-term operation, XPS tests were performed on the manganese-based composite catalysts of the examples and comparative examples to analyze the valence state distribution of Mn (Mn 2+ / Mn 3+ / Mn 4+ The ratio of defect oxygen to lattice oxygen in surface O1s was used to evaluate the influence of interface structure on the stability of manganese valence state and the ability to retain oxygen vacancies.

[0100] Table 2 shows the performance comparison before and after 100 hours of operation under 25℃ and high humidity fluctuation conditions.

[0101] Example 1 88.7 84.2 86.4 82.1 0.03→0.05 Comparative Example 1 49.5 36.8 52.3 38.7 0.24→0.33 Example 2 90.5 88.1 89.8 87 0.02→0.03 Example 3 89.6 82.7 87.2 79.4 0.03→0.06 Example 4 89.3 83.5 88 80.6 0.03→0.05

[0102] "Initial" refers to the average value after 2 hours of stable operation; "After 100 hours" refers to the average value of 3 consecutive collections after 100 hours of operation; the change in outlet ozone concentration is the average level change trend monitored throughout the entire operation period.

[0103] As shown in Table 2, after 100 hours of continuous operation under high humidity fluctuations of 40-80%RH, the toluene removal rate of the catalyst in Comparative Example 1 decreased significantly from 49.5% to 36.8%, the CO2 selectivity decreased from 52.3% to 38.7%, and the outlet ozone concentration increased from 0.24ppm to 0.33ppm, showing obvious deactivation and a decrease in ozone depletion capacity. Combined with XPS results, it can be seen that the Mn³⁺ ratio decreased significantly from 0.44 to 0.31, and the area ratio of oxygen vacancy-related O1s defect oxygen peaks decreased from 0.35 to 0.22, indicating that the active sites were significantly passivated.

[0104] The manganese-based composite catalyst of Example 1 showed significantly better stability than that of Comparative Example 1 under the same conditions: the toluene removal rate only decreased slowly from 88.7% to 84.2%, the CO2 selectivity decreased slightly from 86.4% to 82.1%, and the outlet ozone concentration fluctuated slightly between 0.03 and 0.05 ppm.

[0105] Based on Example 1, after introducing different additives, the stability of Re introduced in Example 2, Ni introduced in Example 3, and W introduced in Example 4 differed under high humidity fluctuation and long-term operation conditions: the initial toluene removal rates of Ni introduced in Example 3 and W introduced in Example 4 were 89.6% and 89.3%, respectively, which were close to those of Example 1. However, after 100 hours of operation, they decreased to 82.7% and 83.5%, respectively. The CO2 selectivity decreased from 87.2% and 88.0% to 79.4% and 80.6%, respectively, while the outlet ozone concentration increased to some extent. This indicates that although Ni and W have a promoting effect on ozone activation and intermediate product oxidation in the initial stage, there is still a certain degree of activity decay and ozone utilization efficiency reduction under high humidity fluctuation conditions.

[0106] In contrast, the catalyst of Example 2, which introduced trace amounts of Re, exhibited the best high-humidity stability: the initial toluene removal rate reached 90.5%, and remained at 88.1% after 100 hours of operation; the CO2 selectivity decreased only slightly from 89.8% to 87.0%; and the outlet ozone concentration remained at a low level of 0.02-0.03 ppm with almost no significant increase.

Claims

1. A method for improving the low-temperature catalytic activity of a manganese-based catalyst, characterized in that, Includes the following steps: S1: Dissolve 3.0-4.0 g manganese sulfate monohydrate, 4.0-5.0 g ammonium persulfate, and 10.0-18.0 g ammonium sulfate in 80-140 mL of water. Stir vigorously at room temperature for 0.1-1.0 h, then transfer to a hydrothermal reactor and react hydrothermally at 100-140 °C for 8-24 h. After cooling to room temperature, filter, wash, and dry, then heat to 350-450 °C in air at 2-10 °C / min and hold for 2-6 h to obtain α-MnO2 support containing tunnel cation vacancies. S2. Disperse 1.5-3.0g of the α-MnO2 support containing tunneled cation vacancies obtained in step S1 in 100-500mL of water, add 20-100mL of NaOH aqueous solution with a mass fraction of 0.5-2.0wt%, stir at room temperature for 0.5-2.0h; filter and wash to obtain a moistened activated support; S3. Add 0.2-0.8 g of tetraisopropyl titanate to 50-150 mL of anhydrous ethanol, add 0.05-0.30 g of acetylacetone, and stir at room temperature for 10-30 min to obtain a titanium precursor complex solution; add the wetted activated carrier obtained in step S2 to the titanium precursor complex solution, sonicate for 5-30 min, and stir at room temperature for 20-60 min; then add 30-80 g of 80-95 wt% ethanol aqueous solution dropwise at a rate of 0.5-2.0 mL / min, and continue stirring at room temperature for 1-5 h after the addition is complete; filter, wash, and dry. S4 The solid dried in step S3 is heated to 350-450℃ in air at a rate of 2-10℃ / min and held for 2-6 hours to obtain a manganese-based composite catalyst.

2. The method for improving the low-temperature catalytic activity of manganese-based catalysts as described in claim 1, characterized in that, Step S3 can also be as follows: Add 0.2-0.8 g of tetraisopropyl titanate to 50-150 mL of anhydrous ethanol, add 0.05-0.30 g of acetylacetone, stir at room temperature for 10-30 min to obtain a titanium precursor complex solution; add the moistened activated carrier obtained in step S2 to the titanium precursor complex solution, sonicate for 5-30 min, and stir at room temperature for 20-60 min; then add 30-80 g of a titanium precursor complex solution at a rate of 0.5-2.0 mL / min. Add an 80-95 wt% aqueous ethanol solution dropwise, and continue stirring at room temperature for 1-5 hours after the addition is complete. After filtration, washing, and drying, add the solution to an ethanol solution containing ammonium perrhenate, nickel nitrate, or ammonium metatungstate. Disperse the solution ultrasonically for 5-30 minutes at room temperature and stir for 20-60 minutes. Then, add 30-80 g of an 80-95 wt% aqueous ethanol solution dropwise at a rate of 0.5-2.0 mL / min. After the addition is complete, continue stirring at room temperature for 1-5 hours. Filter, wash, and dry.

3. The method for improving the low-temperature catalytic activity of manganese-based catalysts as described in claim 1 or 2, characterized in that: The hydrothermal reaction temperature in step S1 is 110-130℃, and the hydrothermal time is 10-16h.

4. The method for improving the low-temperature catalytic activity of manganese-based catalysts as described in claim 1 or 2, characterized in that: The drying temperature in step S1 is 90-110℃, and the drying time is 10-16h.

5. The method for improving the low-temperature catalytic activity of manganese-based catalysts as described in claim 1 or 2, characterized in that: In step S1, the calcination heating rate is 3-7℃ / min, the calcination temperature is 380-420℃, and the calcination time is 3-5h.

6. The method for improving the low-temperature catalytic activity of manganese-based catalysts as described in claim 2, characterized in that: The solution containing ammonium perrhenate, nickel nitrate, or ammonium metatungstate in step S3 is an ethanol solution with a mass fraction of 0.005-0.5 wt%.

7. The method for improving the low-temperature catalytic activity of manganese-based catalysts as described in claim 6, characterized in that: The mass fraction of the ammonium perrhenate solution is 0.01-0.05 wt%.

8. The method for improving the low-temperature catalytic activity of manganese-based catalysts as described in claim 6, characterized in that: The nickel nitrate solution has a mass fraction of 0.05-0.2 wt%.

9. The method for improving the low-temperature catalytic activity of manganese-based catalysts as described in claim 6, characterized in that: The mass fraction of the ammonium metatungstate solution is 0.05-0.2 wt%.

10. The method for improving the low-temperature catalytic activity of a manganese-based catalyst as described in claim 1 or 2, characterized in that: The roasting temperature in step S4 is 380-420℃, and the roasting time is 3-5h.

Citation Information

Patent Citations

  • Preparation method of manganese-based cerium-zirconium solid solution capable of replacing noble metal to be applied to VOC (volatile organic compound) catalyst

    CN115382535A

  • Manganese-containing titanium oxide composite catalyst and odor removal method

    CN120693209A